FEATURES OF THE RING ROLLING IN A SMALL BATCH PRODUCTION OF PROFILE RINGS - P. A. Parkhomchik; V. V. Rudy; V. E. Antoniuc (Литьë и металлургия)
Actual problems of application of ring rolling in the conditions of small-lot production in relation to production of dump trucks of the BelAZ line are considered. The special attention is paid to determination of optimum parameters of ring rolling for profile rings.